Analysis of two minimally invasive procedures for osteoporotic vertebral compression fractures with intravertebral cleft: a systematic review and meta-analysis - Wei, Hongyu (J Orthop Surg Res, 2020)
BACKGROUND: A systematic review and meta-analysis to assess the pros and cons of percutaneous vertebroplasty (PVP) versus kyphoplasty (PKP) for osteoporotic vertebral compression fractures (OVCFs) with intravertebral cleft (IVC) including all available evidence from controlled trials. METHODS: Databases including Pubmed, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI), and Wanfang Data were searched to identify relevant studies comparing PVP and PKP for OVCFs with IVC. The outcomes mainly included visual analog scale (VAS), Oswestry Disability Index (ODI), local kyphotic angle (LKA), rate of vertebral height (VH%), and adverse events. RESULTS: Nine studies enrolling 688 patients were eligible for meta-analysis. The results indicated no significant differences between the two groups in the short-and long-term VAS, ODI, LKA, or VH% (P > 0.05). Compared with PVP, PKP was associated with significantly longer operation time (P < 0.05), higher cost (P > 0.05), and more injected cement volume (P < 0.05). In terms of adverse events, PKP has a lower risk of cement leakage (P < 0.05), while with no significant difference in adjacent-level fracture rates (P > 0.05). CONCLUSION: The two procedures have similar short- and long-term pain relief, functional recovery, local kyphosis correction, and vertebral height maintenance in OVCFs with IVC. PKP is superior to PVP for the injected cement volume, and lower cement leakage rate, however, with longer operation time, more fluoroscopy times, and higher cost. Further randomized controlled trials (RCTs) should be conducted to confirm these results.